THE ROLE OF WORK CULTURE IN THE SUCCESS OF BUREAUCRATIC REFORM IN INDONESIAN AGENCY FOR AGRICULTURAL RESEARCH AND DEVELOPMENT - Utami, Nora Purbo; Dirdjosuparto, Sukiswo (Jurnal Aplikasi Manajemen, 2017)
This study aims to determine the effect of work culture and motivation on performance. This study uses secondary data and primary data which was collected through questionnaire's survey from the government employees of Indonesian Agency for Agricultural Research and Development, Ministry of Agriculture. The population in this study a number of 7525 people, while the samples are taken as 176 respondents who are civil servants Balitbangtan. The method of analysis using Structural Equation Modeling (SEM) analysis. According to the method of Partial Least Square (PLS), work culture and motivation have a significant impact on performance. The study also showed that the most dominant factor influencing performance is the motivation. According to this result, Balitbangtan need to continue to improve the application of cultural values and motivation of civil servants because they have a direct impact on performance. Support from the systems, policies, and budgets is required to achieve good performance of employees, which is one indicator of the success of bureaucracy reform program.